Study on the Influence of Missile Cabin on Fragment Velocity under Explosive Detonation Impact - Li, Xin; Wang, Weili; Liang, Zhengfeng; Dong, Jun; Tang, Jiaojiao (Shock and Vibration, 2024)
For the air-to-air missile warhead, there is a cabin with a certain thickness at a distance around the fragments. At present, the influence of missile cabin has not yet been taken into account in the study of fragment velocity. In this paper, based on the law of conservation of energy, the theoretical equation of fragment velocity considering the kinetic energy of cabin debris was deduced. Then, the rationality of the theoretical formula is validated through the static explosion experiments of two prototype warheads, one with a titanium alloy cabin and the other without any cabin. It was found that after the warhead is equipped with the cabin, part of the energy is consumed to drive the cabin debris, resulting in a decrease in fragment velocity, but the velocity of cabin debris was greater than that of fragment of warheads without any cabin. Besides, through numerical simulation, the driving process of fragments and cabin debris during explosive detonation loading of the warhead with the cabin was studied, which can be divided into six stages, and the error between numerical result and experimental value is not more than 4.8%. Finally, the variety regulation of fragment velocity and cabin debris velocity at different interval distances was further studied by numerical simulation. The results indicate that fragment velocity of warheads with cabin at different interval distances is basically the same, but cabin debris velocity decreases with the increase of interval distance. This conclusion can provide a reference for the structural design and fragment velocity evaluation of warheads with cabin.